Differential roles of kallikrein-related peptidase 6 in malignant transformation and ΔNp63β-mediated epithelial-mesenchymal transition of oral squamous cell carcinoma. (December 2017) - Kaneko, Naoki; Kawano, Shintaro; Yasuda, Kaori; Hashiguchi, Yuma; Sakamoto, Taiki; Matsubara, Ryota; Goto, Yuichi; Jinno, Teppei; Maruse, Yasuyuki; Morioka, Masahiko; Hattori, Taichi; Tanaka, Shoichi; et al.
Highlights: ΔNp63β positively regulates KLK6 and PAR2, and negatively regulates PAR1 in OSCC. Up-regulates KLK6-PAR2 and down-regulates PAR1 induces malignant transformation. Down-regulates KLK6-PAR2 and up-regulates PAR1 lead EMT. KLK6 has two different roles in malignant transformation and EMT in OSCC. KLK6 has potential of biomarker and therapeutic target for OSCC. Abstract: We previously reported that epithelial-to-mesenchymal transition (EMT) was mediated by ΔNp63β in oral squamous cell carcinoma (OSCC). In this study, DNA microarray analyses were performed using ΔNp63β-overexpressing OSCC cells to identify genes associated with ΔNp63β-mediated EMT. Thereby, we focused on kallikrein-related peptidase (KLK) 6, most up-regulated following ΔNp63β-overexpression, that activates protease-activated receptors (PARs). In RT-PCR analyses, ΔNp63 was positively associated with KLK6 and PAR2 and negatively with PAR1 in OSCC cells. By ΔNp63 knockdown, KLK6 and PAR2 expression was decreased and PAR1 was increased. Furthermore, KLK6 knockdown led to enhancing migration and invasion, and inhibiting proliferation, suggesting EMT-phenotypes. Although, in the KLK6 or PAR2 knockdown cells, phosphorylation of ERK was reduced, it was restored in the KLK6 knockdown OSCC cells treated with recombinant KLK6 proteins. Immunohistochemistry showed ΔNp63, KLK6, and PAR2 were more strongly expressed in the epithelial dysplasia and central region of OSCC than normal oral epithelium, whereas PAR1 expression was undetectable. Interestingly, at the invasive front of OSCC, ΔNp63, KLK6, and PAR2 were reduced, but PAR1 was elevated. In addition, the OSCC patients with decreasing KLK6 expression at the invasive front had more unfavourable prognosis. These results suggested differential roles of KLK6 in malignant transformation and EMT; high ΔNp63β expression up-regulates KLK6-PAR2 and down-regulates PAR1, inducing malignant transformation in oral epithelium with stimulating proliferation through ERK signal activation. Moreover, KLK6-PAR2 expression is down-regulated and PAR1 is up-regulated when ΔNp63β expression is decreased, leading to EMT with enhancing migration and invasion through ERK signal reduction at the invasive front.